Development and experimental analysis of polymer based composite bipolar plate using Aquila Taguchi optimization: Design of experiments. Issue 8 (6th July 2022) - Raja, S.; Verma, Akarsh; Rangappa, Sanjay Mavinkere; Siengchin, Suchart
Abstract: In the proton exchange membrane fuel cells, the bipolar plates (BPs) are being widely used in multifunctional mode. They have many unique properties, including prevention of coolant and gas leakages, dissipation of heat from active portions, distribution of air, gas, and fuel uniformly, electric current conduction between cell to cell as a chain, etc. This experimental work was intense to fabricate polymer‐based composite bipolar plates using hybrid combinations. Composites are prepared by using carbon black (CB), glass fiber (GF), and graphite (G) with epoxy and silicone resins. The mixing of composite materials with resins is controlled by the Aquila Taguchi optimization (ATO) method through the L16 Orthogonal Array (OA). Mixing parameters are chosen as rotational speed (20, 30, 40, and 50 rpm), mixing time (10, 15, 20, and 25 min), and mixing temperature (25, 30, 35, and 40°C). Influencing these parameters increases the electrical conductivity (S/cm) and flexural strength (MPa) of the newly prepared bipolar plate composites. From this analysis, highest electrical conductivity is obtained, such as 268.361 S/cm. Similarly, extreme flexural strength occurred at 134.90 MPa.